The Development of Student Behavior According to Buddhist Ethics at Phonbok Pudungsastra School, Ban Paen Subdistrict, Phon Na Kaeo District, Sakon Nakhon Province - Tanakaro, Phramahasurasak; Thongpan, Suwin; Wongpornpavan, Chakkapan; Masing, Piyanut (Journal of Graduate MCU KhonKaen Campus, 2024)
This research aims to 1) examine the behavioral problems of students at Phonbok Pudungsastra School, Ban Paen Subdistrict, Phon Na Kaeo District, Sakon Nakhon Province, 2) study the principles of Buddhist ethics used in developing student behavior, and 3) explore the development of student behavior according to Buddhist ethics at Phonbok Pudungsastra School, Ban Paen Subdistrict, Phon Na Kaeo District, Sakon Nakhon Province. This qualitative research utilizes in-depth interviews and behavioral observation as research tools. Key informants include 1 school administrator, 5 teachers, and 12 students, with data analyzed through descriptive methods. The research results were as follows: 1. The behavioral problems of students at Phonbok Pudungsastra School are categorized into five areas: 1) honesty and integrity, 2) discipline, 3) attentiveness in studies, 4) respectfulness, and 5) social and environmental responsibility. 2. The principles of Buddhist ethics used in developing student behavior as follows: 1) 3 Honesty 2) Sekhiyavatara 3) Four influences 4) Six directions 5) Four sangahavatthus. 3. The development of student behavior according to Buddhist ethics at Phonbok Pudungsastra School involves behavioral modification activities: 1) taking precepts and making merit, 2) Dhamma teachings, 3) chanting and spreading loving-kindness, and 4) meditation practice. These activities, conducted over one term (the first term of 2023), resulted in positive behavioral changes among students: 1) increased honesty and integrity, 2) improved discipline, 3) enhanced attentiveness in studies, 4) heightened respectfulness, and 5) greater social and environmental responsibility.